Prolongation of prothrombin time in the presence of rivaroxaban: is this the only cause?. Issue 2 (February 2017) - Sagheer, Safoorah; McRae, Simon
Abstract : Rivaroxaban is an oral direct Xa inhibitor that can lead to prolongation of prothrombin time and activated partial thromboplastin time. However, these basic coagulation tests are not specific for the anticoagulant effect of rivaroxaban and other confounding factors should be considered while interpreting the test results. We report a case of a patient on rivaroxaban, where underlying factor VII deficiency led to confusion in the interpretation of prothrombin time results and delayed her surgery.